Digital thermal monitoring techniques to assess vascular reactivity following finger and brachial occlusions - Melanie Heath; Drew Gourley; Morteza Naghavi; Stanley Klies; Hirofumi Tanaka (The Journal of Clinical Hypertension, 2021)
Abstract Digital thermal monitoring (DTM) is an alternative, noninvasive, methodology to evaluate endothelial function using temperature change on finger as a surrogate measure of the magnitude of vascular reactivity index (VRI). A most recent modification to the technique includes the application of occlusion cuff at the base of a finger. We evaluated the validity of DTM compared with the standard flow‐mediated dilation (FMD) protocol. Thirty‐eight (22 males; 38 ± 15 years) participants were studied. Occlusion cuff was placed over the right antecubital fossa or at the base of the right index finger. Temperature monitors were placed on bilateral index fingers to assess change in temperature throughout 5‐min occlusion and recovery phases. VRI values obtained with the finger occlusion (1.58 ± 0.29 AU) were not significantly different from VRI measured with the brachial artery occlusion (1.55 ± 0.26 AU; p = .47), and the agreement of VRI values was confirmed in the Bland‐Altman plot with a mean difference of −0.03 ± 0.34 (95% confidence interval: −0.15 to 0.09). Shear rateAUCI was significantly correlated with VRI obtained from brachial occlusion (r = .34) and finger occlusion VRI (r = .54; all p < .05). Moreover, brachial FMD was significantly correlated with brachial occlusion VRI (r = .69; p < .05) and finger occlusion VRI (r = .53; p < .05). Therefore, finger‐based VRI may be a valid and novel alternative measure of endothelial function that is more suitable than the standard FMD or hyperemic shear rate for the assessment of endothelial function in the routine clinical setting.